RNA-Binding Proteins Tia-1 and Tiar Link the Phosphorylation of Eif-2α to the Assembly of Mammalian Stress Granules - Kedersha, Nancy L. (The Rockefeller University Press, 1999)
In response to environmental stress, the related RNA-binding proteins TIA-1 and TIAR colocalize with poly(A)(+) RNA at cytoplasmic foci that resemble the stress granules (SGs) that harbor untranslated mRNAs in heat shocked plant cells (Nover et al. 1989; Nover et al. 1983; Scharf et al. 1998). The accumulation of untranslated mRNA at SGs is reversible in cells that recover from a sublethal stress, but irreversible in cells subjected to a lethal stress. We have found that the assembly of TIA-1/R(+) SGs is initiated by the phosphorylation of eIF-2α. A phosphomimetic eIF-2α mutant (S51D) induces the assembly of SGs, whereas a nonphosphorylatable eIF-2α mutant (S51A) prevents the assembly of SGs. The ability of a TIA-1 mutant lacking its RNA-binding domains to function as a transdominant inhibitor of SG formation suggests that this RNA-binding protein acts downstream of the phosphorylation of eIF-2α to promote the sequestration of untranslated mRNAs at SGs. The assembly and disassembly of SGs could regulate the duration of stress- induced translational arrest in cells recovering from environmental stress.